Relationship Between Glycerolipids and Photosynthetic Components During Recovery of Thylakoid Membranes From Nitrogen Starvation-Induced Attenuation in Synechocystis sp. PCC 6803 - Kobayashi, Koichi; Osawa, Yuka; Yoshihara, Akiko; Shimojima, Mie; Awai, Koichiro (Frontiers in Plant Science, 2020)
Thylakoid membranes, the site of photochemical and electron transport reactions of oxygenic photosynthesis, are composed of a myriad of proteins, cofactors including pigments, and glycerolipids. In the non-diazotrophic cyanobacterium Synechocystis sp. PCC 6803, the size and function of thylakoid membranes are reduced under nitrogen (N) starvation but are quickly recovered after N addition to the starved cells. To understand how the functionality of thylakoid membranes are adjusted in response to N status in Synechocystis sp. PCC 6803, we examined changes in thylakoid components and the photosynthetic activity during the N starvation and recovery processes. In N-starved cells, phycobilisome content, photosystem II protein levels and the photosynthetic activity substantially decreased as compared with those in N-sufficient cells. Although the content of chlorophyll (Chl) a, total protein and total glycerolipid also decreased under the N-starved condition based on OD730 reflecting cell density, when based on culture volume, the Chl a and total protein content remained almost constant and total glycerolipid content even increased during N starvation, suggesting that cellular levels of these components decrease under the N-starved condition mainly through dilution due to cell growth. With N addition, the photosynthetic activity quickly recovered, followed by full restoration of photosynthetic pigment and protein levels. The content of phosphatidylglycerol (PG), an essential lipid constituent of both photosystems, increased faster than that of Chl a, whereas the content of glycolipids, the main constituents of the thylakoid lipid bilayer, gradually recovered after N addition. The data indicate differential regulation of PG and glycolipids during the construction of the photosynthetic machinery and regeneration of thylakoid membranes. Of note, addition of PG to the growth medium slightly accelerated the Chl a accumulation in wild-type cells during the recovery process. Because PG is required for the biosynthesis of Chl a and the formation of functional photosystem complexes, rapid PG biosynthesis in response to N acquisition may be required for the rapid formation of the photosynthetic machinery during thylakoid regeneration.